Extension, translation and preliminary validation of the Northoff Scale for Subjective Experience in Catatonia (NSSC) - Brandt, Geva A.; Fritze, Stefan; Krayem, Maria; Daub, Jonas; Volkmer, Sebastian; Kukovic, Jacqueline; Meyer-Lindenberg, Andreas; Northoff, Georg; Kubera, Katharina Maria; Wolf, Robert Christian; Hirjak, Dusan (Schizophrenia research, 2024)
Background - In the last two decades, much neuroscientific research has been done on the pathomechanisms of catatonia. However, catatonic symptoms have mainly been assessed with clinical rating scales based on observer ratings. Although catatonia is often associated with strong affective reactions, the subjective domain of catatonia has simply been neglected in scientific research. - Methods - The main objective of this study was to modify, extend and translate the original German version of the Northoff Scale for Subjective Experience in Catatonia (NSSC) and to examine its preliminary validity and reliability. Data were collected from 28 patients diagnosed with catatonia associated with another mental disorder (6A40) according to ICD-11. Descriptive statistics, correlation coefficients, internal consistency and principal component analysis were employed to address preliminary validity and reliability of the NSSC. - Results - NSSC showed high internal consistency (Cronbach's alpha = 0.92). NSSC total scores were significantly associated with Northoff Catatonia Rating Scale (r = 0.50, p < .01) and Bush Francis Catatonia Rating Scale (r = 0.41, p < .05) thus supporting its concurrent validity. There was no significant association between NSSC total score and Positive and Negative Symptoms Scale total (r = 0.26, p = .09), Brief Psychiatric Rating Scale (r = 0.29, p = .07) and GAF (r = 0.03, p = .43) scores. - Conclusion - The extended version of the NSSC consists of 26 items and was developed to assess the subjective experience of catatonia patients. Preliminary validation of the NSSC revealed good psychometric properties. NSSC is a useful tool for everyday clinical work to assess the subjective experience of catatonia patients.